Is there something missing in this question i dont seem to understand, can anyone help explaining what is required?
During the calculation of the distribution function of $M$, that is $ P(M \leq m)$, there is an independency assumption being used. That is the condition you are missing, it seems like it was forgotten.
$ P(M \geq m) = P(X_1 \geq m, X_2 \geq m, ... X_n \geq m) = $ (missing the independency condition here)
$P(X_1 \geq m)P(X_2 \geq m)...P(X_n \geq m)= (1-m)^n$
So $P(M \leq m) = 1-(1-m)^n$, as usual.
Without the independency condition you cannot proceed further in the calculation, unless you know more about the joint distribution of the $X_i$